Analytical strategy based on the combination of gas chromatography coupled to time-of-flight and hybrid quadrupole time-of-flight mass analyzers for non-target analysis in food packaging. (1st December 2015) - Cherta, L.; Portolés, T.; Pitarch, E.; Beltran, J.; López, F.J.; Calatayud, C.; Company, B.; Hernández, F.
Highlights: Potential of GC–(EI)TOF MS and GC–(APCI)QTOF MS combination. Analysis of PP/EVOH/PP and PP/Al foil/PP materials. Identification of unknown food packaging contaminants. Abstract: The potential of an advanced analytical strategy based on the use of gas chromatography (GC) coupled to high resolution mass spectrometry (HRMS) with two different analyzers and ionization sources has been investigated and applied to the non-target analysis of food packaging contaminants. Initially, the approach based on GC–time-of-flight (TOF) MS with electron ionization (EI) source allowed performing a library search and mass accurate measurements of selected ions. Then, a second analysis was performed using hybrid quadrupole (Q) TOF MS with an atmospheric pressure chemical ionization (APCI) source in order to search for the molecular ion or the protonated molecule and study the fragmentation behavior. This analytical strategy was applied to the analysis of four polypropylene/ethylene vinyl alcohol/polypropylene (PP/EVOH/PP) multilayer trays and one PP/Al foil/PP film, each one subjected to migration assays with the food simulants isooctane and Tenax®, in order to investigate its potential on the determination of migrant substances.